Mona Lisa Gaze Principle - Tamir, Abraham (Social Science Learning Education Journal, 2017)
This article is about Mona Lisaâs gaze where it is accepted for about 500 years that she is looking at her viewers from all directions she is viewed from. However,a thorough experimental study about her view has never been done. As a researcher, the author has decided to check this phenomenon experimentally. 500 people were asked to look at her picture from right, front and left sides. The results were surprising and negate the well-known myth that Mona Lisa looks at the observer from all directions viewed. Only 65% confirmed that Mona Lisa gave back a look to them.In addition 93% confirmed that Mona Lisa was looking at them while observing at her from the right, 72% from the front and 78% from the left. Following this result brought the author to formulate the following principle: âif you look at any detail in a picture and this detail turns to you, it will turn from each direction you view it: from right,from front, from left, from above and from below.However, from your looking direction the element does not turn to you, it will never turn to you.â Thus, donât view a picture only from the front. Move from right to left and the opposite and you will start to feel that the elements that turned to you from acertain direction will start to âmoveâ in your brain to every direction from which you view them